Induksi Tunas Ubi Kayu (Mannihot esculentaCrantz.) var. Adira 2 Secara In vitro - Khumaida, Nurul; Fauzi, Ahmad Rifqi (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2013)
The research aim was to evaluate the effect of culture medium compositon and BAP concentration on growth and shoot multiplication of in vitro-grown cassava (Mannihot esculentaCrantz.) var. ‘Adira 2’. The experimental design was completely randomize design with two factors. The first factor was composition of basal medium including MS and ½ MS (half of macro and micro nutrients), and the second factor was concentration of BAP (0, 0.5, 1, 1.5, and 3 ppm). The result showed that basal medium MS was the best medium to induce shoot multiplication of cassava var. ‘Adira 2’ with 1.27 shoots explant-1. BAP concentrations had no significant effect on some variables including number of shoot, leaf, node, and height of shoot. However, the BAP concentration affected the number of root explant-1. The control treatment medium (without BAP) showed the best growth of root with 1.95 roots explant-1. Keywords: cassava, BAP, MS medium, tissue culture